2011
DOI: 10.1172/jci46305
|View full text |Cite
|
Sign up to set email alerts
|

IRS2 increases mitochondrial dysfunction and oxidative stress in a mouse model of Huntington disease

Abstract: Aging is a major risk factor for the progression of neurodegenerative diseases, including Huntington disease (HD). Reduced neuronal IGF1 or Irs2 signaling have been shown to extend life span in mice. To determine whether Irs2 signaling modulates neurodegeneration in HD, we genetically modulated Irs2 concentrations in the R6/2 mouse model of HD. Increasing Irs2 levels in the brains of R6/2 mice significantly reduced life span and increased neuronal oxidative stress and mitochondrial dysfunction. In contrast, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 84 publications
2
80
2
Order By: Relevance
“…Another study demonstrated that p-(Ser473)Akt was unchanged in YAC128 and in R6/2 HD mice, but the levels of p-(Ser421)Htt were decreased in the striatum of YAC128 mice and in cells expressing mHtt [79]. In contrast, insulin receptor substrate (IRS)-2, which activates PI-3K/Akt and mTOR cascade, promoted mitochondrial dysfunction and oxidative stress in R6/2 mice; however, in the same study, the authors showed that IRS-2 protein levels were unchanged in the striatum of patients with grade II HD [80]. Conversely, IRS-2 activation induced by insulin, IGF-1 and interleukin-4 enhanced exon1Htt clearance in a dosedependent manner [81].…”
Section: Discussionmentioning
confidence: 91%
“…Another study demonstrated that p-(Ser473)Akt was unchanged in YAC128 and in R6/2 HD mice, but the levels of p-(Ser421)Htt were decreased in the striatum of YAC128 mice and in cells expressing mHtt [79]. In contrast, insulin receptor substrate (IRS)-2, which activates PI-3K/Akt and mTOR cascade, promoted mitochondrial dysfunction and oxidative stress in R6/2 mice; however, in the same study, the authors showed that IRS-2 protein levels were unchanged in the striatum of patients with grade II HD [80]. Conversely, IRS-2 activation induced by insulin, IGF-1 and interleukin-4 enhanced exon1Htt clearance in a dosedependent manner [81].…”
Section: Discussionmentioning
confidence: 91%
“…Irs2 -/-mice exhibit peripheral insulin resistance and progress toward type 2 diabetes because of pancreatic β cell failure. Furthermore, decreased IRS2 protein levels resulted in increased autophagy in the brain and attenuated the progress of Huntington's disease in a transgenic mouse model by decreasing the number of protein aggregates (30). Together, these studies suggest a predominant role for IRS1 in the regulation of somatic growth and for IRS2 in the regulation of metabolism (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 81%
“…Oxidative mitochondrial damage in cardiac I/R injury has been implicated as a cause of cell death (66), but the prevention of heme accumulation and nonfunctional protein aggregates that lead to a cycle of oxidative stress and deterioration of mitochondrial function is clearly protective (67). There is further evidence that energy depletion together with ROS and protein aggregation induces autophagy (68,69).…”
Section: Discussionmentioning
confidence: 99%